Assessment of microcirculation variables and endothelial glycocalyx using sidestream dark field videomicroscopy in anesthetized dogs undergoing cardiopulmonary bypass - Diaz, Devon M.; Orton, E. Christopher; de Rezende, Marlis L.; Zersen, Kristin; Guillaumin, Julien (Frontiers in Veterinary Science, 2023)
Introduction To evaluate microcirculation and endothelial glycocalyx (eGC) variables using sidestream darkfield (SDF) videomicroscopy in canine cardiopulmonary bypass (CPB). Methods Dogs undergoing CPB for surgical correction of naturally-occurring cardiac disease were prospectively included. Variables collected included patient demographics, underlying cardiac disease, red blood cell flow (Flow), 4-25 μm vessel density (Density), absolute capillary blood volume (CBVabs), relative capillary blood volume (CBVrel) and eGC width assessed by perfused boundary region (PBR). Anesthetized healthy dogs were used as control. Microcirculation and eGC variables were compared at baseline under anesthesia (T0), on CPB prior to cross clamping (T1), after cross clamp removal following surgical correction (T2) and at surgical closure (T3). Results Twelve dogs were enrolled, including 10 with a complete dataset. Median Flow was 233.9, 79.9, 164.3, and 136.1 μm/s at T0, T1, T2, and T3, respectively, (p = 1.00). Median Density was 173.3, 118.4, 121.0 and 155.4 mm/mm2 at T0, T1, T2, and T3, respectively, (p = 1.00). Median CBVabs decreased over time: 7.4, 6.6, 4.8 and 4.7 103μm3 at T0, T1, T2, and T3, respectively, (p < 0.01). Median CBVrel increased over time: 1.1, 1.5,1.1, and 1.3 103μm3 at T0, T1, T2, and T3, respectively, (p < 0.001). Median PBR increased over time: 1.8, 2.1, 2.4, 2.1 μm at T0, T1, T2, and T3, respectively, (p < 0.001). Compared to control dogs (n = 8), CPB dogs had lower CBVabs at T0. Conclusion Alterations in eGC thickness and microvascular occur in dogs undergoing CPB for naturally-occurring cardiac disease.